Late glacial and holocene palaeovegetation and palaeogeography of Eastern Fennoscandia - Elina, Galina A.; Lukashov, Anatoly D.; Yurkovskaya, Tatyana K. (Finnish Environment Institute, 2013)
The monograph is a generalization based on the analysis and synthesis of the voluminous scope of data on the dynamics of palaeovegetation and its mapping, along with aspects of palaeogeography of the Kola Peninsula and Karelia. All the elements of past landscapes are considered against the background of the present state of environments: geology, geomorphology and vegetation. The interval under consideration embraces the Late Glacial Time (12 000-10 300 years BP) and the Holocene (from 10 300 years BP up to the present). The book discusses the methodical and theoretical treatments of the last decade. As a result, the dynamics of past landscapes are shown in the unity of all their components (i.e., relief, hydrology and vegetation), and in comparison with their present-day parameters. Cartographic and textual materials on geology and modern vegetation as well as palaeovegetation maps of model territories used in this book are entirely original. The model territories are rather evenly distributed throughout the Kola Peninsula and Karelia. Seven of them are represented in this work; for each of model territory, a series of maps (for 10 500, 9 500, 8 500, 5 500, 3 000, and 1 000 years BP) are provided, correlated with relief and present-day vegetation. The second stage of data generalization is a comparison of maps related to the same temporal sections. The sequence of the maps from ‘older’ to ‘younger’ characterizes the dynamics of chorological palaeovegetation units. These dynamics readily illustrate shifts of geographical zones in space and time.